Tonsillectomy Improved Therapeutic Response in Anti-SRP Myopathy With Chronic Tonsillitis - Ikeda, Takuya; Takeuchi, Hideyuki; Takahashi, Keita; Nakamura, Haruko; Kunii, Misako; Katsumoto, Atsuko; Tada, Mikiko; Higashiyama, Yuichi; Hibiya, Takashi; Suzuki, Shigeaki; Nishino, Ichizo; Koyano, Shigeru; et al. (Frontiers in Immunology, 2020)
Chronic tonsillitis has been attracted attention as a source of abnormal immune responses and a possible trigger of autoimmune diseases such as IgA nephritis, IgA vasculitis, palmoplantar pustulosis, psoriasis, rheumatoid arthritis, Behçet’s disease, and myositis. Here we present the first report of anti–signal recognition particle antibody–associated necrotizing myopathy (anti-SRP myopathy) with IgA nephropathy and chronic tonsillitis in which the therapeutic response to intravenous immunoglobulin (IVIG) treatment was dramatically improved after tonsillectomy and accompanied by a rapid increase in ΔIgG, defined as the change in serum IgG levels 2 weeks after the start of IVIG treatment relative to pre-treatment levels. Moreover, serum anti-SRP antibody titers became undetectable after tonsillectomy even though the resected tonsils did not produce anti-SRP antibodies. Tonsillectomy should be considered when chronic tonsillitis is observed in patients with autoimmune diseases showing poor response to treatment, including anti-SRP myopathy.